Skylark - Oldfield, Jenny; Hunt, Paul (Hodder Children's London, 2001)
A wild and dangerous mountain setting and a daughter who lives, breathes and sleeps horses is a recipe for trouble for ranch owner Sandy Scott. But Kirstie is undaunted by her mother's warnings and loves riding through the trails of Meltwater Range